CONTROL OF THE TECHNICAL CONDITION OF HYDRAULIC TRANSMISSION UNITS OF MOBILE MACHINES ON THE BASIS OF MONITORING THE LEVEL OF CLEANLINESS OF THE WORKING FLUID - Мельянцов, Петро (SWorldJournal, 2024)
The organizational and technological components of the planned and preventive system for maintaining and restoring the working condition of hydraulic transmissions of mobile machines do not meet modern requirements for ensuring their operational reliabil